One equation that you could make is 5+2-(-3)
The answer is B The function shown on the graph has a smaller rate of change but a higher starting point
Answer:
Step-by-step explanation:
4)
Given the expression
a+b-c
substituting the values in the expression
a+b-c = 4.1+5.7-0.3
= 9.8 - 0.3
= 9.5
5)
Given the expression
10-(a+b)
substituting the values in the expression
10-(a+b) = 10 - (4.1+5.7)
= 10 - 9.8
= 0.2
6)
Given the expression
b-c+2
substituting the values in the expression
b-c+2 = 5.7 - 0.3 +2
= 5.4 + 2
= 7.4